Author and Coauthor Responsibilities. Issue 6 (November 2021) - Simpson, Kathleen Rice
Abstract : At MCN we welcome manuscripts from early career nurse scholars. It is important for all authors and coauthors to be aware of authorship criteria and responsibilities. MCN follows the recommendations of the International Committee of Medical Journal Editors for attributing authorship, coauthorship, and acknowledgement of non-author contributors. Sometimes an acknowledgment is more appropriate if coauthors do not meet all criteria. A discussion of recent author and coauthor issues is presented and how to promote nurse scholarship.